Applications of Topological Methods in Molecular Chemistry - Chauvin, Remi; Lepetit, Christine; Silvi, Bernard; Alikhani, Esmail (Challenges and Advances in Computational Chemistry and Physics, 2016)
This is the first edited volume that features two important frameworks, Hückel and quantum chemical topological analyses. The contributors, which include an array of academics of international distinction, describe recent applications of such topological methods to various fields and topics that provide the reader with the current state-of-the-art and give a flavour of the wide range of their potentialities.